Digital inclusion for social inclusion. Case study on digital literacy - Méndez-Domínguez, Paula; Carbonero Muñoz, Domingo; Raya Díez, Esther; Castillo De Mesa, Joaquín (Frontiers in Communication, 2023)
The aim of this research is to identify the differences in access to technologies and digital skills of the population according to their socioeconomic characteristics and to analyse the opportunities offered by new emerging learning environments to promote the social inclusion of vulnerable groups. The digital divide is defined as inequality in the access, use, or impact of information and communication technologies (ICT), and, to address it, it is necessary to build on the conceptual frameworks developed in research to date.This study seeks to 1) identify the main difficulties in digital access and skills and 2) explore what the adoption, design, development, and adaptation of emerging learning technologies mean for the most disadvantaged groups.A quantitative, research design was used. The results obtained show that there are differences in digital skills and access according to education and income level. Different statistical analyses were used, such as non-parametric tests and tests of association between variables. The survey was carried out on a proportional sample of 400 people in La Rioja (Spain). Data was collected through online and face-to-face surveys.A quantitative approach was implemented in the first phase. In the second phase, students of the Social Work degree programme, social work professionals, and users of the Senior Citizens' Centre (elderly people) were included. The qualitative research is based on the development of digital literacy, which seeks to test and provide new insights into the use of innovative learning-teaching methodologies, with digital materials (micro videos), to promote the use and knowledge of ICT as a means of bridging social (as well as digital) divides.